2018
DOI: 10.1007/s00784-017-2324-7
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Zataria extract mouthwash for the management of radiation-induced oral mucositis in patients: a randomized placebo-controlled double-blind study

Abstract: The use of ZM mouthwash effectively decreases the severity of oral complications induced by ionizing radiation in patients during radiotherapy and resulted in high oral quality care. Graphical abstract ᅟ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
1
14
1
1
Order By: Relevance
“…This can be due to differences in the type of treatment regimen used to treat patients with different cancers in the mentioned study, while in the present study, colon cancer patients were treated with FOLFOX regimen. In a study conducted by Aghamohammadi et al in 2017 to determine the effect of Zataria multiflora extract on the prevention and reduction of oral mucositis in patients with head and neck cancer treated with local radiotherapy, they showed that the incidence of mucositis in the intervention group was significantly lower than that in the control group (25). The result of this study is inconsistent with the findings of the present study in terms of the mucositis incidence in the intervention and control groups.…”
Section: Discussioncontrasting
confidence: 99%
“…This can be due to differences in the type of treatment regimen used to treat patients with different cancers in the mentioned study, while in the present study, colon cancer patients were treated with FOLFOX regimen. In a study conducted by Aghamohammadi et al in 2017 to determine the effect of Zataria multiflora extract on the prevention and reduction of oral mucositis in patients with head and neck cancer treated with local radiotherapy, they showed that the incidence of mucositis in the intervention group was significantly lower than that in the control group (25). The result of this study is inconsistent with the findings of the present study in terms of the mucositis incidence in the intervention and control groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients using the SN oil as a mouthwash had a significantly lower OM severity than those in the control group who are treated with a Magic mouthwash formula from weeks 3 to 7 of treatment. These results were in tune with many previously reported data about the efficacy of many natural compounds in the prevention and alleviation of RT or chemo-RT induced OM [16][17][18]. Many compounds have been tried to reduce or prevent RT-induced OM [19][20][21]; however, the clinical practice demonstrates various attitudes towards the use of an accepted medication for minimization and prevention of OM.…”
Section: Discussionsupporting
confidence: 86%
“…Aghamohammadi et al [ 12 ] demonstrated that a mouthwash based on Zataria extracts affected the incidence of grade 3–4 oral mucositis to a relative risk ratio of 0.432 and also had a significant effect on the patient’s pain symptomatology.…”
Section: Resultsmentioning
confidence: 99%